2010
DOI: 10.1021/ja106291e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Probes That Selectively Recognize the Earliest Aβ Oligomers in Complex Mixtures

Abstract: Alzheimer’s disease (AD) is characterized by the self-assembly of amyloid beta (Aβ) peptides. Recent models implicate some of the earliest Aβ oligomers, such as trimers and tetramers, in disease. However, the roles of these structures remain uncertain, in part, because selective probes of their formation are not available. Towards that goal, we generated bivalent versions of the known Aβ ligand, the pentapeptide KLVFF. We found that compounds containing sufficiently long linkers (~19 to 24 Å) recognized primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Furthermore, recent insights have indicated that small oligomeric assemblies of Aβ, in contrast to monomeric and fibrillar species, are toxic for neuronal synapses and exist in cerebrospinal fluid sample from AD patient at higher concentration level than from control individual [6][7][8]. Thus, Aβ oligomer (AβO) comprising of 50-100 Aβ monomers has been regarded as a reliable molecular biomarker for AD diagnosis and the crucial target for therapeutic intervention [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent insights have indicated that small oligomeric assemblies of Aβ, in contrast to monomeric and fibrillar species, are toxic for neuronal synapses and exist in cerebrospinal fluid sample from AD patient at higher concentration level than from control individual [6][7][8]. Thus, Aβ oligomer (AβO) comprising of 50-100 Aβ monomers has been regarded as a reliable molecular biomarker for AD diagnosis and the crucial target for therapeutic intervention [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The multivalent structures containing the KLVFF segment [61][63] target the LMW oligomers through assumed incorporation into the β-sheet structure. The selective interaction with LMW oligomers have been demonstrated for dimeric structures [62]. The aggregation process could also be inhibited this way, but protecting effects against the toxic Aβ oligomers have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…The tested antibodies include 6E10, 4G8, anti-Ab (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 9F1, recognizing Ab M1-K16, Ab L17-E22, Ab E22-M35 and Ab I32-V39, respectively. The tested antibodies include 6E10, 4G8, anti-Ab (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 9F1, recognizing Ab M1-K16, Ab L17-E22, Ab E22-M35 and Ab I32-V39, respectively.…”
Section: Ab Binding Of Klvfwakmentioning
confidence: 99%
“…The physiological Ab concentration is in the range of low nM in brain 22,52,65 and low pM in body fluids, 66,67 requiring higher sensitivity for reliable in vivo or ex vivo detection using KLVFWAK. While multivalent peptide ligands for Ab were previously developed based on KLVFF, 31,33,70 their functional affinity and specificity were difficult to optimize systematically. For example, one may consider increasing Ab aggregate-affinity by exploiting multivalency of KLVFWAK.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation